Attitudinal modalities of citizenship representation styles in Georgia. Issue 2 (July 2019) - Mestvirishvili, Maia
This study investigates citizenship representation styles and their compositional modalities in contemporary Georgia. The article starts with a discussion of legal, social, and political influences that shaped conceptions of citizenship in post-Soviet countries, including Georgia. The study presents the results of a survey of 700 students from 10 universities in Georgia. They completed questionnaires exploring citizenship styles and associated predictor variables. The study suggests that a cultural citizenship style is dominant among Georgian students. It is best predicted by the level of national identification, followed by patriotism, nationalism, in-group attitudes, and religious orthodoxy. The data also show the opposing roles of nationalism and patriotism on ethnic and civic citizenship styles. The article argues that a cultural citizenship representation style could be the compromise solution in the ethnic versus civic citizenship dichotomy and might be more appropriate for societies characterized by ethno-nationalist tendencies.